Extrusão por fricção sob alta razão de extrusão de resíduos de usinagem da liga AA6082 - Ignácio, Guilherme Poy (Universidade Federal de São Carlos, 2025)
This study investigates the variations in mechanical and microstructural properties during the extrusion of fine wires from AA6082 alloy chips under a high extrusion ratio, with an emphasis on the impact of processing conditions. The process conditions, such as speed, torque, and temperature, varied throughout the extrusion, resulting in significant changes in both the mechanical properties and the microstructural evolution of the material. The results highlight that the use of high extrusion ratios (greater than 1000) was effective in promoting a homogeneous refinement of the microstructure throughout the entire length of the extruded wire, regardless of variations in processing parameters. In terms of mechanical properties, the extruded samples exhibited an Ultimate Tensile Strength (UTS) of 265 MPa, a fracture elongation of 9.8%, and a microhardness of 98 HV0.2, values comparable to the material in the T4 condition. Hardness, tensile strength, and elongation were strongly influenced by the temperature characteristic of the process, with hardness being attributed to the formation of precipitates and the latter two due to the presence of defects. However, the study revealed that temperature plays a crucial role in the degradation of the mechanical properties of the material. Starting from the seventh meter of extrusion, a reduction in mechanical properties was observed, with a severe degradation after the thirteenth meter. This behavior was attributed to the increase in temperature, which approached the material’s melting temperature, compromising the process stability and the integrity of the extrudate. Temperature analysis, using a thermocouple placed 1 mm from the surface of the die, indicated that the actual temperature at the contact interface could have been even higher, exacerbating the thermal effects. The temperature rise was also exacerbated by the form of the feedstock. The use of chips as raw material resulted in a significant temperature increase due to the high surface area of contact and the friction between particles, intensified by the high rotational speeds of the process. This is consistent with previous studies that report that using chips increases the temperature of the process compared to other types of feedstock. The high extrusion ratio was considered a critical parameter, promoting homogeneous grain refinement throughout the radius of the extruded wire, a behavior distinct from that observed in larger diameter extrudates. vi Hardness tests indicated the formation of precipitates during extrusion, in line with previous findings, but suggested the need for further investigations into the precipitation kinetics in 6xxx series alloys under non-conventional heat treatment conditions. Additionally, it was highlighted that phenomena inherent to friction extrusion, such as severe plastic deformation (SPD), dynamic recrystallization, and heat generation, directly influence the microstructure and mechanical properties of the material. Based on the findings, temperature control was identified as a crucial factor to ensure process stability and maintain the mechanical properties of the material throughout the extrusion process.
Friction extrusion of AA6082 alloy machining waste under a high extrusion ratio
Keywords: Extrusão por fricção; Deformação plástica severa; Liga AA6082; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO